Analysis of Trading Behaviour on Discrete GPU Market : Autoregressive Conditional Duration Approach - Douda, Matyáš; Tomanová, Petra; Holý, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
This bachelor thesis analyses the trading behaviour on the discrete GPU market. First duopoly of AMD and Nvidia is introduced, then its relation with Bitcoin is established in a basic overview. Next, theoretical foundation for Autoregressive Conditional Duration family of models and distributions is given. The empirical part of the thesis first cleans the data then estimates an optimal model for the data from NYSE. The estimated model is then used to analyse the impact of significant events on the observed stocks with an emphasis on changes in Bitcoin price. In conclusion, correlation between both stocks and Bitcoin price has been established.
Vedoucí práce: Petra Tomanová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses